Diet quality and genetic association with body mass index: results from 3 observational studies. Issue 6 (22nd October 2018) - Ding, Ming; Ellervik, Christina; Huang, Tao; Jensen, Majken K; Curhan, Gary C; Pasquale, Louis R; Kang, Jae H; Wiggs, Janey L; Hunter, David J; Willett, Walter C; Rimm, Eric B; Kraft, Peter; et al.
ABSTRACT: Background: It is unknown whether dietary quality modifies genetic association with body mass index (BMI). Objective: This study examined whether dietary quality modifies genetic association with BMI. Design: We calculated 3 diet quality scores including the Alternative Healthy Eating Index 2010 (AHEI-2010), the Alternative Mediterranean Diet score (AMED), and the Dietary Approach to Stop Hypertension (DASH) diet score. We examined the interactions of a genetic risk score (GRS) based on 97 BMI-associated variants with the 3 diet quality scores on BMI in 30, 904 participants from 3 large cohorts. Results: We found significant interactions between total GRS and all 3 diet scores on BMI assessed after 2–3 y, with an attenuated genetic effect observed in individuals with healthier diets (AHEI: P -interaction = 0.003; AMED: P = 0.001; DASH: P = 0.004). For example, the difference in BMI (kg/m 2 ) per 10-unit increment of the GRS was smaller among participants in the highest tertile of AHEI score compared with those in the lowest tertile (0.84; 95% CI: 0.72, 0.96 compared with 1.14; 95% CI: 0.99, 1.29). Results were consistent across the 3 cohorts with no significant heterogeneity. The interactions with diet scores on BMI appeared more significant for central nervous system GRSs ( P < 0.01 for 3 diet scores) than for non–central nervous system GRSs ( P > 0.05 for 3 diet scores). Conclusions: A higher diet quality attenuated genetic predisposition to obesity. These findings underscore the importance of maintaining a healthful diet for the prevention of obesity, particularly for those individuals with a strong genetic predisposition to obesity. This trial was registered with the Clinical Trial Registry as NCT03577639.